Kontroversi Maulid Nabi Muhammad SAW dalam Pandangan As-Suyuthi dan Ibnu Taimiyah - Salman Alfarisy; Ahmad Faris; Aribuddin Aribuddin (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2023)
This research examines the controversy surrounding the legality of celebrating Maulid Nabi Muhammad SAW through a comparative analysis of two prominent medieval Islamic scholars: Imam As-Suyuthi and Imam Ibnu Taimiyah. The Maulid tradition has been practiced since the Middle Ages and remains debated in contemporary Islamic discourse. This study addresses two primary questions: first, what are the respective views of Imam As-Suyuthi and Imam Ibnu Taimiyah regarding the celebration of Maulid Nabi Muhammad SAW; second, how do the argumentative strengths of these two scholars compare in supporting their positions. Employing library research methodology with a descriptive-analytical approach, this study analyzes relevant Islamic literature and classical texts to construct a comprehensive comparison. The findings reveal that Imam As-Suyuthi categorizes Maulid celebration as bid'ah hasanah (commendable innovation), permissible when conducted with praiseworthy activities such as Quranic recitation and salawat upon the Prophet. He distinguishes between bid'ah hasanah and bid'ah dalalah (misguided innovation), arguing that not all innovations are prohibited. Conversely, Imam Ibnu Taimiyah rejects Maulid celebration entirely, categorizing it as bid'ah (religious innovation) that should be avoided. His argument rests on the principle that if Maulid were religiously meritorious, the Prophet's Companions and the Salaf al-Salih would have practiced it. This study contributes to understanding the theological foundations underlying divergent scholarly opinions on Maulid and their implications for contemporary Islamic practice.